PERBANDINGAN DAN HUBUNGAN ANTARA BOBOT BADAN DAN BOBOT ORGAN SALURAN PENCERNAAN PADA DUA BANGSA SAPI - Ria Anjalani; Sumardyan Wisnubroto; Paulini Paulini (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This study aimed to compare and to determine the difference in the relationship between the weight of the digestive tract organs with the body weight of bali cattle and limousine cattle at the same age and sex.. Sampling was carried out by purposive sampling. Data of body weight and digestive tract organs of Bali cattle and Limousin cattle were analyzed using t-test. The relationship between digestive tract organs weight and body weight correlation analysis using correlation test. The effect of digestive tract organ weight on body weight was analyzed using a simple linear regression test. The results of this study showed that body weight and digestive tract organ weights in bali cattle and limousine cattle had significant differences (P<0.05). The weight of the rumen reticulum and large intestine had a strong relationship with body weight in bali cattle (r = 0.638; r = 0.761) compared to the weight of other digestive tract organs. The weight of the rumen reticulum has a strong relationship with the body weight of limousine cattle (r = 0.684) compared to other digestive tract organs. The regression model between body weight and the weight of the rumen reticulum and large intestine in bali cattle were y = 39,962x + 124.86 (r2=0,407) and y = 64,501x +78,928 (r2=0,579). The regression model between body weight and rumen reticulum weight in Bali cattle was y = 23,152x+281,06 (r2=0,467). The two breeds of cattle have differences in body weight, the weight of the digestive tract organs, and the relationship between body weight and the weight of the digestive tract organs.